Coronavirus Pandemic – SARS-CoV-2 in Orthopedics and Trauma Surgery - Müller, Michael; Stöckle, Ulrich; Trampuz, Andrej; Felix, Stephan; Kramer, Axel; Wassilew, Georgi (Zeitschrift für Orthopädie und Unfallchirurgie, 2020)
The corona virus has spread worldwide since it first appeared in China and represents a pandemic of unprecedented magnitude. The pandemic has not only social and economic effects, but even more impressive effects on the health system. If the virus spreads uncontrollably and rapidly, there is a risk of an unpredictable increase of patients with COVID-19 disease requiring hospital treatment. The capacities of a hospital can quickly reach the limit and consequently patients can no longer be adequately treated. Therefore, in the acute phase of the pandemic, it is necessary to release all hospital resources for the treatment of COVID-19 patients. Strict hygiene regulations must also be observed in order to prevent the virus from spreading unexpectedly in the hospital in order to protect patients and hospital staff. Elective operations and outpatient clinics must be cancelled in the acute phase. Special hygiene measures must be observed for urgent and unpostponable operations. These relate to the admission of the patients, the accommodation in the ward and the operative care in the operating room. In the post-acute phase, a normal surgical program can be resumed step by step. In this phase, however, clear hygiene regulations must also be observed. Regular medical meetings taking into account the current pandemic situation and the occurrence of new infections must be carried out in the hospital and the occupancy of the ward and operating room adjusted accordingly. To what extent the situation for the treatment of patients in orthopedics and trauma surgery will normalize cannot be predicted at the present time.
Keywords: corona virus pandemic; SARS-CoV-2; orthopedics; traumatology; COVID-19